Scales for Measuring Ageism as Experienced by Older Adults: Literature Review and Methodological Critique - Kang, Hyun (Frontiers in Education, 2022)
This study identified the existing ageism scales and reviewed the literature on ageism scales with an emphasis on the methodological issues. Most standardized ageism scales have focused on younger people’s attitudes and beliefs toward older adults. There are relatively few standardized scales that assess how older adults feel and think about their experiences being stereotyped. Although significant efforts have been made to outline ageism’s various dimensions and constructs, these efforts have not led to a common consensus on ageism and its characteristics. Lack of consensus, in turn, makes it harder to develop a standardized scale. The findings suggest that a new scale that applies only to measuring ageism as perceived by older adults and corresponds to the significant dimensions of ageism must be developed. The preliminary results of this mini-review will serve as the basis for further research on the ageism scale among older adults.